A laser composite strengthening method for steam turbine blade based on preset carbon source film
Patent Information
- Application Number
- CN202611227558.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明在克服现有汽轮机叶片激光熔覆强化工艺存在的碳化物含量低、颗粒分布不均、强化效果差的缺陷,提供一种基于预置碳源薄膜的汽轮机叶片激光复合强化方法
复合碳源供给,大幅提升碳化物体积分数:本发明采用“磁控溅射非晶碳膜+微量石墨粉”复合碳源体系,碳膜经激光瞬时高温分解产生的碳原子活性远高于传统粉末碳源,可充分与金属涂层发生原位反应,生成大量碳化物,同时石墨粉补充碳源生成碳化物,相较于传统直接熔覆工艺,涂层碳化物体积分数提升40%以上,强化效果显著提升。
Smart Images

Figure CN122979893A_ABST
Abstract
Description
Technical Field
[0001] This invention patent relates to the field of turbine blade surface strengthening technology, and in particular to a laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film. Background Technology
[0002] Turbine blades are the core components of steam turbine generator sets. They operate under conditions of high-speed airflow, water vapor erosion, and alternating loads for extended periods, making them highly susceptible to failures such as surface wear, water erosion, and fatigue cracking. These failures directly affect the operational stability and service life of the steam turbine generator set. Therefore, extremely high requirements are placed on the surface strength, water erosion resistance, and fatigue resistance of the blades.
[0003] Laser cladding, with its advantages of high metallurgical bonding strength between the coating and the substrate, significant strengthening effect, and strong process adaptability, has become one of the mainstream research and application directions for surface strengthening of turbine blades. Laser powder / wire feeding cladding is used to clad nickel-based, cobalt-based, or iron-based alloys onto the surface of stainless steel substrates. Sometimes, ceramic particles or in-situ self-generated ceramic dispersion phase materials are added to improve the surface hardness, wear resistance, and water erosion resistance of the blades. However, on the one hand, directly introducing carbide particles can easily lead to particle agglomeration and uneven distribution, resulting in problems such as large-size carbide segregation, high coating porosity, and crack defects, reducing the coating's density and mechanical properties. On the other hand, carbide particles have poor wettability with metals, and poor interfacial bonding is prone to occur during laser cladding, significantly reducing the bonding strength between the coating and the blade substrate. Furthermore, the in-situ reaction method for forming carbides has a single carbon source supply method, low carbon element activity, limited carbide generation, and uncontrollable size and morphology. Ultimately, this results in a low carbide volume fraction and insufficient blade surface strengthening effect, which cannot meet the long-cycle, high-load service requirements of high-end steam turbine blades. Summary of the Invention
[0004] This invention overcomes the shortcomings of existing laser cladding strengthening processes for steam turbine blades, such as low carbide content, uneven particle distribution, and poor strengthening effect. It provides a laser composite strengthening method for steam turbine blades based on a pre-placed carbon source film. By employing a composite carbon source supply method combining magnetron sputtering of a pre-placed high-purity amorphous carbon film with trace amounts of graphite powder for carbon supplementation, and in conjunction with secondary laser cladding, a carbide strengthening layer is generated. This effectively improves the carbide volume fraction, density, and mechanical properties of the coating. Simultaneously, a solid solution strengthening layer serves as a transition between the carbide layer and the substrate, improving the interfacial bonding strength and enhancing the wear resistance, high-temperature resistance, and corrosion resistance of the steam turbine blades.
[0005] This invention provides a laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film: Pre-treat the blade surface; A metal solution coating was prepared on the pretreated blade surface by laser cladding; A high-purity carbon source film is pre-placed on the surface of the metal solid solution coating by magnetron sputtering. A small amount of high-purity graphite powder is uniformly brushed onto the surface of the pre-placed amorphous carbon film to form a graphite carbon supplement layer. Laser cladding is performed on the surface of the blade with pre-applied carbon film and graphite carbon supplementation layer.
[0006] Furthermore, the laser cladding selects a metal powder that is completely dissolved in the iron matrix, wherein the metal powder is metallic chromium, or a single metal powder or a mixture of multiple metal powders.
[0007] Furthermore, the high-purity carbon source film is a high-purity amorphous carbon film, and the thickness of the carbon film is controlled to be 80~150nm.
[0008] Furthermore, the magnetron sputtering process parameters are set as follows: sputtering power 150~250W, working gas pressure 0.8~1.5Pa, argon flow rate 30~50sccm, and sputtering time 10~30min.
[0009] Furthermore, the graphite powder in the carbonized graphite layer has a particle size of 200-400 mesh.
[0010] Furthermore, laser cladding treatment is performed on the blade surface with pre-applied carbon film and graphite carbon supplementation layer, including: The instantaneous high-energy thermal effect of laser is used to decompose the carbon film and release highly active carbon atoms. The highly active carbon atoms react in situ with Cr, V and Zr in the coating to generate carbides. The surface graphite powder slowly decomposes to replenish carbon and reacts to generate some carbides, which strengthen the coating.
[0011] Furthermore, a metal solid solution coating is prepared on the pretreated blade surface by laser cladding. The laser cladding process parameters are: laser power 1800~2400W, scanning speed 6~12mm / s, powder feed rate 12~18g / min, and spot diameter 3~6mm. The prepared metal coating thickness is 0.3~0.8mm, and the coating is free of cracks, pores, and inclusion defects.
[0012] Furthermore, the blade surface with pre-applied carbon film and graphite carbon supplementation layer is subjected to laser cladding treatment with a laser power of 1500~2000W, a scanning speed of 8~15mm / s, and a spot diameter of 4~7mm.
[0013] The beneficial effects of this invention are as follows: Composite carbon source supply significantly increases carbide volume fraction: This invention adopts a composite carbon source system of "magnetron sputtering amorphous carbon film + trace amount of graphite powder". The carbon atoms generated by the instantaneous high temperature decomposition of the carbon film by laser have a much higher activity than traditional powder carbon sources. They can fully react with the metal coating in situ to generate a large number of carbides. At the same time, graphite powder supplements the carbon source to generate carbides. Compared with the traditional direct cladding process, the carbide volume fraction of the coating is increased by more than 40%, and the strengthening effect is significantly improved.
[0014] High coating bonding strength and long service life: The process of first cladding a metal solid solution coating and then generating carbides in situ creates a metal solid solution layer transition between the carbide layer and the metal, achieving gradient transition and metallurgical bonding, and solving the problems of poor interface bonding and easy peeling caused by the introduction of traditional carbide powder.
[0015] Minimal heat-affected zone and no damage to the substrate: The heat input of the secondary laser cladding is controllable, the heat-affected zone is small, and it will not damage the mechanical properties of the turbine blade substrate. The deformation of the blade after processing is minimal, and no subsequent correction treatment is required. The processing efficiency is high and the yield is high. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the turbine blade surface strengthening process of the present invention; Figure 2 A schematic diagram of the cross-sectional SEM morphology of the carbide coating on the surface of 304 stainless steel; Figure 3 This is a schematic diagram of the SEM morphology of the coating on the surface of 304 stainless steel. Detailed Implementation
[0017] The present invention will be further described below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and should not be used to limit the scope of protection of the present invention.
[0018] like Figure 1 As shown, this invention provides a laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film, using stainless steel turbine blades as the substrate, and mainly includes the following steps: S1. Substrate pretreatment: Grinding, polishing, and degreasing cleaning are performed on the stainless steel surface of the turbine blades to remove the surface oxide layer, oil stains, impurities and defects, ensuring the flatness and cleanliness of the blade surface, and drying for later use. S2. Preparation of metal solid solution coating by laser cladding: Select metal powder that can be completely dissolved in the iron substrate. The preferred metal powder is chromium, but single metal powders such as V and Zr or mixed metal powders can also be used. The metal solid solution coating is prepared by laser cladding on the pretreated stainless steel surface, achieving metallurgical bonding with the substrate. The structure is dense and uniform, providing a metal matrix for subsequent in-situ carbide reaction. S3. Pre-depositing a high-purity carbon source film by magnetron sputtering: A high-purity amorphous carbon film is pre-deposited on the surface of the metal coating prepared in step S2 using magnetron sputtering technology. The thickness of the carbon film is controlled to be 80~150nm. The magnetron sputtering process parameters are set as follows: sputtering power 150~250W, working pressure 0.8~1.5Pa, argon flow rate 30~50sccm, and sputtering time 10~30min, to ensure that the carbon film is uniformly, densely, and adheres to the surface of the metal coating without peeling. S4. Auxiliary carbon supplementation pretreatment: A small amount of high-purity graphite powder is uniformly brushed onto the coating surface of the pre-formed amorphous carbon film as a supplementary carbon source. The graphite powder has a particle size of 200~400 mesh, and the coating thickness is uniform and does not accumulate, which makes up for the problem of insufficient total carbon source of the film and is suitable for the growth requirements of large-size carbides. S5. Secondary Laser Composite Cladding Strengthening: Laser cladding is applied to the blade surface with a pre-applied carbon film and a graphite carbon supplement layer. Utilizing the instantaneous high-energy thermal effect of the laser, the surface amorphous carbon film rapidly decomposes within milliseconds, releasing highly active carbon atoms. These highly active carbon atoms react in situ with metal elements such as Cr, V, and Zr in the underlying metal coating, generating a large amount of carbides. Simultaneously, the surface graphite powder slowly decomposes and supplements carbon, reacting to generate some carbides, ultimately resulting in a high-volume-fraction carbide-strengthened coating. Furthermore, a metal solid solution layer is retained between this layer and the substrate, forming a gradient transition in microstructure and properties, and a metallurgical bond.
[0019] As a preferred option, the laser cladding process parameters in step S2 are: laser power 1800~2400W, scanning speed 6~12mm / s, powder feeding amount 12~18g / min, spot diameter 3~6mm, the prepared metal coating thickness is 0.3~0.8mm, and the coating is free of cracks, pores, inclusions and defects.
[0020] As a preferred option, the secondary laser cladding process parameters in step S5 are: laser power 1500~2000W, scanning speed 8~15mm / s, spot diameter 4~7mm, and heat input is lower than that of the first metal cladding process to avoid overheating of the coating and coarse grains, and to ensure stable in-situ reaction. Example 1
[0021] This embodiment provides a laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film, using conventional 304 stainless steel turbine blades as the substrate, suitable for use in turbines operating under conventional conditions, and includes the following steps: S1. Substrate pretreatment: The blade surface is sanded with 800# and 1200# sandpaper in sequence to remove oxide scale and surface scratches. After fine polishing with a polishing machine, it is ultrasonically cleaned with anhydrous ethanol for 15 minutes to remove surface oil and dust. It is then placed in a drying oven at 60℃ to dry for later use. S2. Laser Cladding of Cr Metal Coating: Cr metal powder with a purity ≥ 99.5% is selected, and a metal coating is prepared using laser cladding technology. Process parameters: laser power 2000W, scanning speed 8mm / s, powder feed rate 15g / min, spot diameter 4mm. A Cr metal coating with a thickness of 0.5mm is prepared. Figure 2 As shown, the coating has good metallurgical bonding, dense structure, and no defects; S3. Pre-formed carbon film by magnetron sputtering: Amorphous carbon film is pre-formed on the surface of Cr metal coating using DC magnetron sputtering equipment. Process parameters: sputtering power 200W, working pressure 1.0Pa, argon flow rate 40sccm, sputtering time 20min. The carbon film thickness is 110nm. The carbon film is uniform, dense, and has no peeling or damage. S4. Auxiliary carbon supplementation treatment: Select 300-mesh high-purity graphite powder and evenly coat it thinly on the surface of the carbon film. The coating is thin and does not accumulate, serving as an auxiliary carbon source. S5. Secondary Laser Composite Strengthening: Secondary cladding is performed using laser cladding equipment. Process parameters: laser power 1800W, scanning speed 10mm / s, spot diameter 5mm. Utilizing the instantaneous high-energy thermal effect of the laser, the 110nm amorphous carbon film on the surface decomposes rapidly in milliseconds, releasing highly active carbon atoms. These atoms undergo an in-situ metallurgical reaction with the underlying Cr metal solid solution coating, generating a large number of fine and dispersed Cr7C3 and Cr23C6 hard carbides. Simultaneously, the 300-mesh high-purity graphite powder on the surface slowly and continuously decomposes to replenish carbon elements, growing a suitable amount of large-sized carbides. The coarse and fine carbides combine to form a high-volume-fraction carbide-strengthened surface layer. The heat input of this secondary laser cladding is lower than that of the first cladding, and it will not completely consume the underlying Cr solid solution layer, thus retaining a complete metal solid solution transition layer between the coating and the substrate. Figure 3 As shown, a gradient microstructure of "stainless steel matrix - metal solid solution transition layer - high carbide strengthening layer" is formed, realizing the performance gradient transition and high-strength metallurgical combination, and completing the composite strengthening treatment of the blade. Example 2
[0022] This embodiment provides a laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film, using high-temperature resistant 316L stainless steel turbine blades as the substrate, suitable for use in high-temperature and high-pressure turbines, and includes the following steps: S1. Substrate pretreatment: Mechanically grind and polish the blade surface to remove the surface oxide layer and rust, ultrasonically clean with anhydrous ethanol for 20 minutes, and dry with cold air for later use. S2. Laser cladding V-Zr composite metal coating: V powder and Zr powder with a purity ≥99.5% are mixed at a mass ratio of 8:2, and a composite metal coating is prepared by laser cladding process. Process parameters: laser power 2200W, scanning speed 10mm / s, powder feed rate 16g / min, spot diameter 5mm, coating thickness 0.6mm. S3. Magnetron sputtering of pre-formed carbon film: Magnetron sputtering process parameters: sputtering power 220W, working pressure 1.2Pa, argon flow rate 45sccm, sputtering time 25min, to prepare a high-purity amorphous carbon film with a thickness of 130nm. S4. Auxiliary carbon supplementation treatment: Apply a thin, uniform layer of 250-mesh high-purity graphite powder for carbon supplementation. S5. Secondary Laser Composite Strengthening: Laser power 1900W, scanning speed 12mm / s, spot diameter 6mm. The laser's instantaneous high temperature excites the rapid decomposition of the surface 130nm amorphous carbon film, releasing highly active carbon atoms. These atoms react in situ with the underlying V-Zr composite metal solid solution layer, generating high-melting-point hard carbides such as VC and ZrC. 250-mesh graphite powder on the surface continuously replenishes carbon, assisting in the formation of large-size carbides and further increasing the overall carbide content. The secondary laser's heat input is controllable, reacting and modifying only the surface carbon source and shallow metal layer, while the underlying V-Zr metal solid solution transition layer is fully preserved, forming a gradient composite strengthening structure. This effectively alleviates interfacial stress, improves the coating's high-temperature resistance and erosion resistance, and makes it suitable for use in harsh high-temperature conditions. Example 3
[0023] This embodiment uses 420 stainless steel turbine blades as the base material to strengthen turbine blades suitable for heavy-load, high-speed erosion, and high-wear conditions, and includes the following specific steps: S1. Substrate pretreatment: The blade surface is polished step by step with 800#, 1200# and 2000# sandpaper to remove the surface hardening layer, oxide scale and minor defects. After mirror polishing, the blade is ultrasonically cleaned for 20 minutes with a mixture of anhydrous ethanol and acetone to thoroughly remove surface oil and impurities. The blade is then dried at room temperature with cold air for later use.
[0024] S2. Preparation of trimetallic solid solution coating by laser cladding: Select Cr powder, V powder and Zr powder with a purity ≥99.5% and mix them uniformly in a mass ratio of 7:2:1. Prepare a composite metal solid solution coating by laser cladding process. Process parameters: laser power 2400W, scanning speed 6mm / s, powder feed rate 18g / min, spot diameter 6mm. Prepare a coating thickness of 0.8mm. The coating is metallurgically bonded to the substrate, with a uniform and dense structure, and no cracks, pores or inclusions.
[0025] S3. Magnetron sputtering of pre-placed high-purity carbon source film: A DC magnetron sputtering device is used to pre-place a high-purity amorphous carbon film on the surface of the tri-metal composite coating. Process parameters: sputtering power 250W, working pressure 1.5Pa, argon flow rate 50sccm, sputtering time 30min. The prepared carbon film thickness is 150nm. The carbon film is uniform, dense, has strong adhesion, and is free from peeling and damage.
[0026] S4. Auxiliary carbon replenishment pretreatment: Select 400-mesh high-purity graphite powder, apply it evenly and thinly to the surface of the carbon film, ensuring uniform coating thickness without accumulation, accurately replenishing the carbon source, adapting to the growth requirements of multi-metal carbides, and ensuring the uniform generation of large-size carbides.
[0027] S5. Secondary Laser Composite Cladding Strengthening: Secondary strengthening is performed using laser cladding equipment. Process parameters: laser power 2000W, scanning speed 8mm / s, spot diameter 7mm. Under the millisecond-level instantaneous high energy of the laser, the thick amorphous carbon film rapidly decomposes to generate a large number of highly active carbon atoms, which couple and react in situ with the Cr, V, and Zr multi-metal elements within the coating to generate multi-element composite hard carbides. Combined with continuous carbon replenishment using graphite powder, the volume fraction of the carbides is significantly increased. The process strictly controls the heat input, preserving the complete tri-metallic solid solution transition layer at the bottom, forming a gradient microstructure, and balancing the coating's high hardness, high wear resistance, and interfacial bonding stability.
[0028] Performance testing and comparative analysis of various embodiments (1) Coating hardness: The average hardness of the coating in Example 1 was 2.8 times higher than that of the 304 substrate; the average hardness of the coating in Example 2 was 3.2 times higher than that of the 316L substrate; the average hardness of the coating in Example 3 was 3.5 times higher than that of the 420 substrate. Compared with the traditional cladding coating, the hardness was increased by 15%~25%, and the strengthening effect increased in a gradient.
[0029] (2) Wear and corrosion resistance: The wear rate of the coatings in each embodiment is reduced by more than 30% compared with the traditional cladding coatings. Among them, the heavy-duty wear resistance of embodiment 3 is the best. At the same time, the gradient transition structure effectively eliminates interface defects, and the coatings have significantly better resistance to water vapor corrosion and high-temperature oxidation than the traditional single-layer cladding coatings.
[0030] (3) Interface bonding and structural stability: All embodiments of the present invention retain the metal solid solution transition layer to form a gradient transition metallurgical bonding structure, which completely solves the problems of stress concentration and easy peeling at the interface of traditional carbide coatings. The bonding strength between the coating and the substrate is increased by more than 30% compared with the traditional process. After processing, the coating is free of cracks, pores and peeling, and has excellent structural stability.
[0031] In summary, this invention utilizes a pre-placed carbon source thin film composite in-situ reaction process, combined with a metal solid solution gradient transition structure, to flexibly adapt to single-metal, bimetallic, and multi-metal coating systems according to different substrates and operating conditions. It effectively solves the technical pain points of traditional laser cladding, such as low carbide content, uneven microstructure, and poor interface performance. It is suitable for strengthening turbine blades in various scenarios, including conventional, high-temperature, and heavy-load applications, and has a wide range of engineering applications and extremely high practical value.
[0032] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A laser composite strengthening method for turbine blades based on a pre-placed carbon source thin film, characterized in that: Pre-treat the blade surface; A metal solution coating was prepared on the pretreated blade surface by laser cladding; A high-purity carbon source film is pre-placed on the surface of the metal solid solution coating by magnetron sputtering. A small amount of high-purity graphite powder is uniformly brushed onto the surface of the pre-placed amorphous carbon film to form a graphite carbon supplement layer. Laser cladding is performed on the surface of the blade with pre-applied carbon film and graphite carbon supplementation layer.
2. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that: Laser cladding uses metal powder that is completely dissolved in the iron matrix. The metal powder is metallic chromium, or a single metal powder or a mixture of multiple metal powders.
3. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that: The high-purity carbon source film is a high-purity amorphous carbon film, and the thickness of the carbon film is controlled to be 80~150nm.
4. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that: The magnetron sputtering process parameters are set as follows: sputtering power 150~250W, working gas pressure 0.8~1.5Pa, argon flow rate 30~50sccm, and sputtering time 10~30min.
5. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that: The graphite powder used for the carbon supplement layer has a particle size of 200~400 mesh.
6. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that, Laser cladding treatment of blade surfaces with pre-applied carbon film and graphite carbon supplementation layer includes: The instantaneous high-energy thermal effect of laser is used to decompose the carbon film and release highly active carbon atoms. The highly active carbon atoms react in situ with Cr, V and Zr in the coating to generate carbides. The surface graphite powder slowly decomposes to replenish carbon and reacts to generate some carbides, which strengthen the coating.
7. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that, The pretreated blade surface was treated with a metal solid solution coating by laser cladding. The laser cladding process parameters were: laser power 1800~2400W, scanning speed 6~12mm / s, powder feed rate 12~18g / min, and spot diameter 3~6mm. The thickness of the prepared metal coating was 0.3~0.8mm, and the coating was free of cracks, pores, and inclusion defects.
8. The method for laser composite strengthening of turbine blades based on a pre-placed carbon source thin film according to claim 1, characterized in that, Laser cladding is performed on the surface of blades with pre-applied carbon film and graphite carbon supplementation layer. The laser power is 1500~2000W, the scanning speed is 8~15mm / s, and the spot diameter is 4~7mm.